Successful management of a patient with toxic epidermal necrolysis by high dose intravenous immunoglobulin. Issue 4 (2013) - Güneş, Ali; Yolbaş, İlyas and Kelekçi, Selvi and Yel, Servet and Şahin, Cahit and Ece, Aydın
No abstract available